Diversity-oriented synthesis of peptide-boronic acids by a versatile building-block approach - Hinkes, Stefan; Kämmerer, Severin; Klein, Christian D. (Chemical science, 2020)
A new strategy for the synthesis of peptide-boronic acids (PBAs) is presented. 20 Fmoc-protected natural amino acids with orthogonal side-chain protection were straightforwardly converted into their corresponding boron analogues in three simple steps. Subsequent immobilisation on commercially available 1-glycerol polystyrene resin and on-resin transformations yielded a diversity of sequences in high purity. The strategy eliminates various synthetic obstacles such as multi-step routes, low yields, and inseparable impurities. The described method comprises great potential to be implemented in automated combinatorial approaches by markedly facilitating the access to a variety of PBAs. The coupling of amino acids or other building blocks with α-aminoboronates allows the creation of hybrid molecules with significant potential in various scientific disciplines, such as medicinal chemistry, structural biology, and materials science.